#### Answer

$(f\circ g\circ h)(x)=6x^2+1.$

#### Work Step by Step

We are given $f(x)=3x+4$, $g(x)=2x-1$, and $h(x)=x^2$.
So: $$(f\circ g\circ h)(x)=f(g(h(x)))=f(g(x^2))=f(2x^2-1)=3(2x^2-1)+4\\=6x^2-3+4 =6x^2+1.$$

Published by
Pearson

ISBN 10:
0-32187-896-5

ISBN 13:
978-0-32187-896-0

$(f\circ g\circ h)(x)=6x^2+1.$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.